2023
DOI: 10.3389/fendo.2023.1103949
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 21-gene expression assay on treatment decisions and clinical outcomes in breast cancer with one to three positive lymph nodes

Abstract: BackgroundTo assess the practice patterns of the recurrence score (RS) based on the 21-gene expression assay on adjuvant chemotherapy recommendations and survival outcomes in estrogen receptor-positive (ER+)/HER2- breast cancer (BC) with one to three positive lymph nodes (N1).MethodsWe included patients with T1-2N1M0 and ER+/HER2- BC diagnosed between 2010 and 2015 in the Surveillance, Epidemiology, and End Results Oncotype DX Database. Breast cancer-specific survival (BCSS) and overall survival (OS) were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Compounds that selectively inhibit the above-mentioned metabolic adaptations have shown promise in preclinical articles and clinical trials, providing hope for more effective and less toxic treatment options. Furthermore, understanding the genetic underpinnings of breast cancer has allowed for the development of targeted therapies that exploit vulnerabilities in cancer cells driven by specific genetic mutations ( 41 , 42 ), which further enriches the available treatment methods.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds that selectively inhibit the above-mentioned metabolic adaptations have shown promise in preclinical articles and clinical trials, providing hope for more effective and less toxic treatment options. Furthermore, understanding the genetic underpinnings of breast cancer has allowed for the development of targeted therapies that exploit vulnerabilities in cancer cells driven by specific genetic mutations ( 41 , 42 ), which further enriches the available treatment methods.…”
Section: Discussionmentioning
confidence: 99%
“…139 Recent initiatives such as the TAILORx trial have demonstrated the potential for gene expression proling to guide treatment decisions and optimise outcomes. 140 7.2.2. Combination therapies.…”
Section: Perspectives On the Future Of Targeted Drug Delivery In Brea...mentioning
confidence: 99%